The Influence Micorhyza Arbuscular Indigenous to Growth Pepper Plant (Pipper nigrum L.) - Yanti Yanti; La Aba (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Pepper is a plantation commodity that belongs to the spice category and has an important role in Indonesia's economic growth. Southeast Sulawesi is one of the centers for the development of pepper plants, especially in the South Konawe area. The purpose of this study was to determine the effect of indigenous mycorrhizae on the growth of pepper plants which were carried out in Sindangkasih Village, West Ranomeeto District, South Konawe Regency. Analysis of dry weight and infection of indigenous mycorrhizae on the roots of pepper plants was carried out at the Agrotechnology Laboratory, Faculty of Agriculture, University of Haluoleo Kendari. Data analysis in this study used a single factor Randomized Block Design (RBD) with 4 treatments and 3 replications, so there were 12 trials. The treatment consisted of 4 levels, namely without mycorrhizae (A0), 10 grams of mycorrhizae (A1), 15 grams of mycorrhizae (A2) and 20 grams of mycorrhizae (A3). The results showed that the application of indigenous arbuscular mycorrhizae had an effect on the growth parameters of pepper plants in the form of plant height, number of leaves and number of tendrils, where A3 produced higher plant height, number of leaves and number of tendrils and was significantly different from other treatments. Treatment A2 was not significantly different from treatment A1 but significantly different from treatment A0 (without mycorrhiza). Mycorrhizal inoculation of 20 grams/polybag can cause root infection of pepper plants to increase by 80.00%.